Battery and electric equipment

By adjusting the electrolyte composition and tab structure parameters, the problem of lithium deposition on the negative tab of a three-tab lithium battery was solved, improving the battery's conductivity and chemical stability, and enhancing its charge/discharge performance and safety.

CN121149355APending Publication Date: 2025-12-16ZHUHAI COSMX BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511270701.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-05
Publication Date
2025-12-16

AI Technical Summary

Technical Problem

In lithium batteries with a three-tab structure, the instantaneous current density at the negative tab is high during charging, which leads to severe local lithium plating at the negative tab, affecting battery performance and safety.

Method used

By adjusting the mass percentage A of carboxylic acid ester solvent in the electrolyte and the ratio B of the total solder area of ​​the negative electrode tab to the area of ​​the negative electrode tab groove (A/B≥2), and by adding nitrile additives and sulfur-containing additives, the composition of the electrolyte is optimized, the conductivity and wettability of the electrolyte are improved, and physical obstacles at the electrode tab solder joints are reduced.

Benefits of technology

It significantly improves the lithium plating problem at the tab sites, enhances the battery's ion conductivity and chemical stability, reduces internal resistance, strengthens the battery's fast charging and rate performance, and improves the battery's safety and cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121149355A_ABST
    Figure CN121149355A_ABST
Patent Text Reader

Abstract

The invention provides a battery and electric equipment, the battery comprises an electrolyte, an organic solvent in the electrolyte comprises ethyl propionate and propyl propionate, a positive plate is provided with at least two positive tabs, and a negative plate comprises a negative current collector and a negative active layer arranged on the negative current collector. Part of the negative electrode current collector is exposed out of the negative electrode active layer and forms a negative electrode lug groove, a negative electrode lug is welded in the negative electrode lug groove, the battery meets the condition that A / B is larger than or equal to 2, and when the amount of the carboxylic ester solvent added into the electrolyte is adjusted and meets the relation of the ratio of the total welding printing area of the negative electrode lug to the area of the negative electrode lug groove, the total welding printing area of the negative electrode lug is larger than or equal to 2. And lithium precipitation at a negative electrode lug position can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium battery technology, and more particularly to a battery and an electrical device. Background Technology

[0002] Lithium-ion batteries, as a high-efficiency and green energy storage solution, have been widely used in many fields. Among them, the three-tab structure battery, with its unique design, can achieve more efficient energy transfer and thermal management inside the battery, thus having a longer service life and better safety performance.

[0003] A three-tab battery cell typically refers to a cell with two tabs on the positive electrode and one tab on the negative electrode. The extra positive tab provides an additional electrical contact point, effectively shortening the average electron conduction path during discharge. This allows the battery to release more charge in a shorter time, significantly reducing internal resistance and improving fast charging and rate performance. However, this also means that during charging, there is only one negative tab compared to the positive tab, resulting in a higher instantaneous current density at the negative tab. This can exacerbate the problem of localized lithium plating at the negative tab.

[0004] Therefore, how to alleviate the lithium plating problem in batteries is a technical problem that urgently needs to be solved by those skilled in the art. Summary of the Invention

[0005] This invention provides a battery and an electrical device. By adjusting the mass percentage A of the carboxylic acid ester solvent added to the electrolyte, when it satisfies the relationship between the total solder area of ​​the negative electrode tab and the area of ​​the negative electrode tab groove B: A / B≥2, the battery can significantly improve the conductivity of the electrolyte while improving the wettability of the electrolyte, thereby accelerating the migration rate of the electrolyte and improving the lithium plating problem.

[0006] This invention provides a battery comprising a positive electrode, a negative electrode, and an electrolyte. The organic solvent in the electrolyte includes ethyl propionate and propyl propionate. The positive electrode has at least two positive tabs. The negative electrode includes a negative current collector and a negative active layer disposed on the negative current collector. The negative active layer exposes a portion of the negative current collector and forms a negative tab groove. A negative tab is welded into the negative tab groove. The battery satisfies Formula 1:

[0007] A / B≥2 Equation 1

[0008] In Formula 1, A is the sum of the mass percentages of ethyl propionate and propyl propionate in the electrolyte, expressed as %; B is the ratio of the total solder area of ​​the negative electrode tabs to the area of ​​the negative electrode tab groove on the negative electrode sheet of the battery, expressed as %; wherein, the total solder area of ​​the negative electrode tabs refers to the sum of the areas of all solder marks at the connection between the negative electrode tabs and the negative electrode current collector; and the area of ​​the negative electrode tab groove refers to the current collector area enclosed by the three sides of the negative electrode tab groove and the edge of the negative electrode current collector.

[0009] In the battery described above, the negative electrode tab groove has a negative electrode active layer on three sides, and B is 5%-35%;

[0010] And / or, the total solder area of ​​the negative electrode tab is 15 mm²-50 mm², and the area of ​​the negative electrode tab groove is 150 mm²-300 mm². 2 .

[0011] In the battery described above, the electrolyte further includes nitrile additives, wherein the nitrile additives are one or more selected from adiponitrile, 1,3,6-hexanetrionitrile, and butadionitrile, and the nitrile additives satisfy Formula 2:

[0012] 5C / B≥1 Equation 2

[0013] In Formula 2, C represents the mass percentage of nitrile additives in the electrolyte, expressed as %.

[0014] For batteries as described above, C is 0.5%-10%.

[0015] In the battery described above, the electrolyte further includes a sulfur-containing additive, which is one or more of 1,3-propenesulfonate lactone, 1,3-propanesulfonate lactone, and BDTD, wherein the BDTD comprises at least one compound with the following structure:

[0016] Formula 1, Equation 2, Formula 3,

[0017] Equation 4, Equation 5, Formula 6,

[0018] Equation 7, Formula 8, Formula 9,

[0019] Formula 10, Equation 11, Equation 12,

[0020] The sulfur-containing additive has a mass percentage content of 0.1%-6% in the electrolyte.

[0021] For batteries as described above, A is 10%-80%;

[0022] And / or, the electrolyte further includes difluoroethyl acetate, wherein the mass percentage of difluoroethyl acetate in the electrolyte is 3-50%.

[0023] In the battery described above, the electrolyte includes a negative electrode film-forming agent, which includes fluoroethylene carbonate and / or lithium difluoroborate oxalate.

[0024] The mass ratio of the fluoroethylene carbonate to lithium difluoroborate oxalate is ≥10:1;

[0025] And / or, the fluoroethylene carbonate has a mass percentage content of 2%-30% in the electrolyte, and the lithium difluoroborate oxalate has a mass percentage content of 0.1%-3% in the electrolyte.

[0026] In the battery described above, the negative electrode sheet comprises silicon-carbon material, the mass of which is 1%-50% of the total mass of the negative electrode active material; and the electrolyte contains 10%-30% fluoroethylene carbonate by mass.

[0027] The present invention also provides an electrical device, including the battery described above.

[0028] The present invention provides a battery, an electrical device, a positive electrode, a negative electrode, and an electrolyte, wherein A is the mass percentage of ethyl propionate and propyl propionate in the electrolyte, and B is the ratio of the total solder area of ​​the negative electrode tab to the area of ​​the negative electrode tab groove on the negative electrode sheet of the battery. The negative electrode tab groove is a recessed structure relative to the active layer, and the flow of electrolyte is usually relatively smooth. However, the total solder area of ​​the negative electrode tab and the negative electrode tab groove will affect the flow of electrolyte. Therefore, the value of B reflects the proportion of the total solder area of ​​the tab in the negative electrode tab groove. The larger the value, the stronger the resistance to electrolyte. Therefore, by adjusting the relationship between A and B to satisfy A / B≥2, the problem of poor electrolyte wettability at the tab solder joint caused by the physical barrier formed by the tab solder inside the electrode can be reduced, the situation of increased lithium plating in the present invention can be improved, the ion transport speed can be accelerated, and the local lithium plating at the tab site can be effectively improved. Attached Figure Description

[0029] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0030] Figure 1 This is a schematic diagram of the structure of a battery negative electrode sheet with a single soldering position provided by the present invention;

[0031] Figure 2 This is a schematic diagram of the structure of a battery negative electrode sheet with multiple solder pads provided by the present invention;

[0032] Figure 3 This is a schematic diagram of the structure of the positive electrode sheet of the battery provided by the present invention.

[0033] Explanation of reference numerals in the attached figures:

[0034] 1: Negative electrode sheet; 11: Negative electrode current collector; 12: Negative electrode active layer. Detailed Implementation

[0035] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0036] Lithium-ion batteries with a three-tab structure can improve the overall charge and discharge capacity of the cell by shortening the average conduction path of electrons. However, due to the special location of the negative tab welding point, the instantaneous current density of the negative tab reaches its maximum during charging. Furthermore, the local physical barriers at the welding point location can affect the wetting of the electrolyte, which further aggravates the lithium plating problem at the negative tab.

[0037] Therefore, embodiments of the present invention provide a battery comprising a positive electrode, a negative electrode, and an electrolyte. The organic solvent in the electrolyte includes ethyl propionate and propyl propionate. The positive electrode has at least two positive tabs. The negative electrode includes a negative current collector and a negative active layer disposed on the negative current collector. The negative active layer exposes a portion of the negative current collector and a negative tab groove. A negative tab is welded into the negative tab groove. The battery satisfies Formula 1:

[0038] A / B≥2 Equation 1

[0039] In Formula 1, A is the sum of the mass percentages of ethyl propionate and propyl propionate in the electrolyte, expressed as %; B is the ratio of the total solder area of ​​the negative electrode tab to the area of ​​the negative electrode tab groove on the negative electrode sheet of the battery, expressed as %; where the total solder area of ​​the negative electrode tab refers to the sum of the areas of all solder marks at the connection between the negative electrode tab and the negative electrode current collector; and the area of ​​the negative electrode tab groove refers to the current collector area enclosed by the three sides of the negative electrode tab groove and the edge of the negative electrode current collector.

[0040] The total solder area of ​​the negative electrode tab refers to the sum of the areas of all solder marks at the connection between the negative electrode tab and the negative current collector. (Refer to...) Figure 1 and Figure 2 The solder marks are the circular / quadrilateral solder areas on the current collector. These solder marks are the paths through which current is conducted from the negative electrode tab to the negative electrode plate. The size of the solder mark area directly affects the current conduction efficiency and the internal resistance of the battery.

[0041] The negative electrode tab slot refers to the space or area reserved for the negative electrode tab in the battery design, such as... Figure 1 and Figure 2 As shown, the negative electrode sheet 1 in this embodiment of the invention includes a negative electrode current collector 11 and a negative electrode active layer 12. The area indicated by the dashed box is the negative electrode tab groove. Its area can affect the layout and welding method of the tab.

[0042] The total solder area of ​​the negative electrode tab is calculated by summing the areas of N solder marks. The area of ​​a single solder mark is calculated as follows: for a quadrilateral: length * width; for a circle: πr², where r is the radius of the circular solder mark. The area of ​​the negative electrode tab groove is calculated as the width * length of the region. Figure 1 and Figure 2 The area indicated by the dashed box.

[0043] The battery of the present invention improves the problem of localized lithium plating at the tab sites during cycling. This is mainly because, firstly, the electrolyte in the battery of the present invention includes ethyl propionate and propyl propionate, both of which have good kinetics. Therefore, using at least one of the substances in A in the electrolyte can improve the electrolyte's conductivity, accelerate the electrolyte migration rate, and improve lithium plating at the tab sites. Furthermore, ethyl propionate has a lower viscosity, while propyl propionate, although having a higher viscosity, has better chemical stability. Therefore, using ethyl propionate and propyl propionate in combination avoids the problem of poor chemical stability associated with using ethyl propionate alone, resulting in a more significant improvement in battery performance and thus improving the lithium plating problem at the tab sites.

[0044] On the other hand, this invention correlates the amount of A with parameter B. By ensuring A / B≥2, the electrolyte can flow more smoothly in the tab solder joint area, effectively improving the problem of poor electrolyte wetting around the tab solder joint, thereby enhancing the battery's ionic conductivity and chemical stability. Equation 1 plays a crucial role in ensuring the coordination between the battery's chemical and mechanical properties, thus overcoming the problem of lithium plating on the tab.

[0045] In one specific embodiment, the battery has two positive tabs on the positive electrode and one negative tab on the negative electrode.

[0046] This invention uses a battery cell with a three-pole structure, see reference. Figure 1 , Figure 2 and Figure 3 , Figure 1 This is a schematic diagram of the structure of a battery negative electrode sheet with a single soldering position provided by the present invention; Figure 2 This is a schematic diagram of the structure of a battery negative electrode sheet with multiple solder pads provided by the present invention, wherein a negative electrode tab is provided at the negative electrode position; Figure 3 This is a schematic diagram of the structure of the positive electrode sheet of the battery provided by the present invention. Two tabs are provided at the positive electrode. The two tabs at the positive electrode can shorten the ion transport path, alleviate polarization heating, and avoid the high resistance problem of the positive electrode when there is only one tab. At the same time, since the amount of A is related to the parameter B, the problem of shortening the average conduction path of electrons caused by the additional tab electrical contact point can be avoided, which significantly reduces the internal resistance of the battery and improves the fast charging and rate performance of the battery. Therefore, the battery with this three-tab structure can avoid the defect of local lithium plating aggravation at the tab site.

[0047] In one specific embodiment, the battery has a negative electrode active layer on three sides of the negative electrode tab groove, with B being 5%-35%;

[0048] For example, B can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, or a range of any two of these values.

[0049] In batteries, a B value in the range of 5-35% is more effective. First, a B value within this range ensures better current distribution in the battery, further reducing the risk of local overheating and improving battery safety. Second, it can further enhance the mechanical connection between the negative electrode tab and the negative electrode plate, thus improving structural stability. In addition, within this range, contact resistance can be reduced more effectively, further improving battery power output.

[0050] In one specific implementation, the total solder area of ​​the negative electrode tab is 15 mm. 2 -50 mm².

[0051] When the total solder area of ​​the negative electrode tab is 15 mm 2 At -50 mm², the current density can be reduced more effectively, thereby reducing resistance loss, improving current conduction efficiency, helping to dissipate heat more effectively, reducing the risk of local overheating, and increasing the solder area can enhance the mechanical connection between the negative electrode tab and the negative electrode sheet, reducing solder failure caused by thermal cycling and mechanical stress.

[0052] In one specific implementation, the negative electrode tab area is 150 mm. 2 -300 mm 2 .

[0053] The negative electrode tab area is 150 mm. 2 At a depth of -300 mm², more flexibility can be provided for the arrangement of the negative electrode tabs, resulting in better current distribution and improving the overall heat dissipation performance of the battery.

[0054] By selecting appropriate solder marks and slot areas within these ranges, this invention can achieve a better balance between the battery's electrical performance, thermal management, and mechanical stability.

[0055] In one specific embodiment, the electrolyte further includes a nitrile additive, which is one or more selected from adiponitrile, 1,3,6-hexanetrionitrile, and butadionitrile, and the nitrile additive satisfies Formula 2:

[0056] 5C / B≥1 Equation 2

[0057] In Equation 2, C represents the mass percentage of the nitrile additive in the electrolyte.

[0058] Because the welding points generated after the electrode tabs are welded will damage the protective layer on the surface of the current collector, the current collector is easily corroded by the electrolyte. The larger the area of ​​the solder mark, the greater the corrosion problem of the negative electrode tab groove. At the same time, the acid and ester solvents in the electrolyte are prone to producing HF due to their poor chemical stability, which will aggravate the corrosion of the solder mark at the negative electrode tab position.

[0059] This invention incorporates nitrile additives into the electrolyte. The lone pair electrons of the cyano functional groups in these additives can form stable chelates with transition metal ions on the positive electrode surface or dissolved metal ions, thereby better reducing the migration of metal ions to the negative electrode and their damage to the interfacial film. Simultaneously, it further blocks active sites that catalyze electrolyte oxidation. Therefore, nitrile additives can better passivate the current collector, providing protection, and also better passivate the positive electrode, protecting the positive electrode interface, inhibiting the catalytic effect of metal dissolution on the carboxylic acid ester solvent, reducing side reactions and HF generation, and significantly improving the high-temperature performance of the battery cell.

[0060] Furthermore, the larger the ratio of the total solder area of ​​the negative electrode tab to the area of ​​the electrode tab groove, the higher the amount of nitrile additives should be. When 5C / B≥1 is satisfied, nitrile additives can better compensate for the influence of the electrode tab solder on the current collector and better passivate the current collector.

[0061] This invention does not specifically limit the source of nitrile compounds; any commercially available products known to those skilled in the art or products prepared by conventional methods are acceptable.

[0062] When the nitrile additive is a mixture of the above-mentioned specific compounds, the present invention does not impose specific limitations on the proportions between the various specific compounds.

[0063] In one specific embodiment, the C content in the battery is 0.5%-10%;

[0064] For example, C can be 0.5%, 1%, 2%, 4%, 6%, 8%, 10%, or a range of any two of these values.

[0065] When the mass percentage (C) of nitrile additives in the electrolyte is 0.5%-10%, it can improve the stability of the electrolyte, further reduce the occurrence of side reactions, and thus extend battery life. Furthermore, this range helps to form a more stable solid electrolyte interface film, which is beneficial for further improving the battery's cycle performance and safety. Therefore, by controlling the C range to 0.5%-10%, a better balance between battery performance and safety can be ensured.

[0066] In one specific embodiment, the electrolyte further includes a sulfur-containing additive, which is one or more of 1,3-propenesulfonate lactone (PST), 1,3-propanesulfonate lactone (PS), and BDTD, wherein BDTD comprises at least one compound with the following structure:

[0067] Formula 1, Equation 2, Formula 3,

[0068] Equation 4, Equation 5, Formula 6,

[0069] Equation 7, Formula 8, Formula 9,

[0070] Formula 10, Equation 11, Equation 12,

[0071] The sulfur-containing additive has a mass percentage content of 0.1%-6% in the electrolyte.

[0072] For example, the mass percentage of sulfur-containing additives in the electrolyte can be 0.1%, 1%, 2%, 3%, 4%, 5%, 6%, or any two of these values.

[0073] This invention incorporates sulfur-containing additives into the electrolyte. These sulfur-containing additives have high oxidation potentials, so when the positive electrode reaches a high voltage, they preferentially undergo oxidative decomposition over organic solvents in the electrolyte (such as ethyl propionate and propyl propionate), thereby depositing an interfacial film on the positive electrode surface. This film hinders direct contact between the electrolyte and the positive electrode material, suppressing side reactions. By controlling the mass percentage of sulfur-containing additives in the electrolyte to 0.1%-6%, the interfacial stability is further improved, significantly enhancing the overall high-temperature performance of the battery cell.

[0074] When the sulfur-containing additive is a mixture of the above-mentioned specific compounds, the present invention does not impose specific limitations on the proportions between the various specific compounds.

[0075] In one specific embodiment, A in this battery is 10%-80%;

[0076] When A in the electrolyte is 10%-80%, it allows for better viscosity adjustment via carboxylic acid esters, thereby improving the electrolyte's conductivity. Furthermore, it enhances the electrolyte's chemical stability and accelerates its migration rate, thus mitigating lithium plating at the tab sites. Therefore, controlling A within the range of 10%-80% to satisfy the relationship with B achieves the best effect in improving lithium plating at the tab sites.

[0077] In one specific embodiment, the electrolyte further includes difluoroethyl acetate (DFEA), wherein the mass percentage of difluoroethyl acetate in the electrolyte is 3%-50%.

[0078] For example, A can be 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, or a range of any two of these values.

[0079] For example, the mass percentage of difluoroethyl acetate in the electrolyte can be 3%, 10%, 20%, 30%, 40%, 50%, or any two of these values.

[0080] Adding DFEA to the electrolyte, which contains F bonds and has good high voltage resistance, can improve the electrolyte's antioxidant properties, making it suitable for high-voltage battery systems. When used in combination with carboxylic acid esters, it can increase the electrolyte's charging window, allowing the electrolyte to maintain high cycle stability even at high voltages.

[0081] This invention does not specifically limit the source of difluoroethyl acetate; any commercially available product or product prepared by conventional methods well known to those skilled in the art is acceptable.

[0082] In one specific embodiment, the electrolyte in the battery includes a negative electrode film-forming agent, which includes fluoroethylene carbonate (FEC) and / or lithium difluoroborate oxalate (LiDFOB).

[0083] The negative electrode film-forming agents FEC and LiDFOB have strong film-forming ability and early reduction potential at the negative electrode. By using these two negative electrode film-forming agents, the negative electrode is provided with dual protection, forming a good interfacial film at the negative electrode, improving the electrochemical stability of carboxylic acid esters, and significantly improving the cycle life and high-temperature performance of the battery cell.

[0084] In one specific embodiment, the mass ratio of fluoroethylene carbonate to lithium difluoroborate oxalate is ≥10:1.

[0085] In this invention, the mass ratio of FEC to LiDFOB is ≥10:1. When this ratio of FEC is achieved, it helps to form a stable solid electrolyte interface film, thereby improving the cycle stability and safety of the battery.

[0086] And / or, the mass percentage of fluoroethylene carbonate in the electrolyte is 2%-30%, preferably, the mass percentage of FEC in the electrolyte is 10%-18%.

[0087] For example, the mass percentage of fluoroethylene carbonate in the electrolyte can be 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, or any two of these values.

[0088] FEC preferentially undergoes reduction and decomposition on the negative electrode surface compared to other solvents in the electrolyte, forming a stable and dense solid electrolyte interface film, reducing the continued decomposition of the electrolyte in subsequent cycles. Within this range, FEC effectively improves the electrochemical stability of the electrolyte, reduces side reactions, and increases the energy density and lifespan of the battery.

[0089] The mass percentage of lithium difluoroborate oxalate in the electrolyte is 0.1%-3%.

[0090] For example, the mass percentage of lithium difluoroborate oxalate in the electrolyte can be 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, or any two of these values.

[0091] LiDFOB has a high reduction potential and preferentially decomposes on the negative electrode surface. Its decomposition products include boron-containing compounds and lithium oxalate salts. These substances together form an interfacial film, thereby protecting the negative electrode, maintaining interfacial stability, and extending cycle life. When the mass percentage of LiDFOB is 0.1-3%, the effect of enhancing the conductivity and thermal stability of the electrolyte is best, further improving the overall performance of the battery.

[0092] This invention ensures the optimal balance between battery performance, stability, and safety by selecting the ratio and range of FEC and LiDFOB.

[0093] This invention does not specifically limit the source of fluoroethylene carbonate and lithium difluoroborate oxalate; products prepared using commercially available products well known to those skilled in the art or by conventional preparation methods are acceptable.

[0094] In one specific embodiment, the battery negative electrode sheet includes silicon-carbon material, the mass of which is 1%-50% of the total mass of the negative electrode active material; the electrolyte contains 10%-30% fluoroethylene carbonate by mass.

[0095] This invention uses silicon-carbon materials to prepare the negative electrode sheet. The silicon-containing negative electrode has extremely high specific capacity, which can significantly improve the volumetric energy density of the battery. However, due to the huge volume effect generated during the insertion and extraction of silicon-carbon negative electrode materials, the polarization and internal resistance of the battery increase significantly during cycling. In contrast, the tab structure has a more uniform overall current density distribution and a significantly increased electron transport speed, resulting in a significant reduction in its internal resistance. This can effectively improve the problems of increased polarization and internal resistance of silicon negative electrodes. Therefore, the tab structure and the silicon-carbon-containing negative electrode can have a synergistic effect, improving battery performance.

[0096] For example, the mass of silicon-carbon material can be 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% of the total mass of the negative electrode active material, or a range of any two of these values.

[0097] In the negative electrode of a battery, excessive silicon content may lead to a shortened cycle life. Therefore, optimizing the silicon-carbon ratio within the range of 1%-50% helps to improve battery capacity while maintaining good cycle life and stability. Thus, by controlling the proportion of silicon-carbon materials within 1%-50%, a good balance can be achieved between improving battery capacity and maintaining battery stability.

[0098] In the electrolyte, free radical electrolytes (FECs) help form a stable solid electrolyte interphase (SEI) film on the negative electrode surface. This film is particularly important for silicon-carbon negative electrodes because silicon undergoes significant volume changes during charge and discharge. This invention uses an FEC content of 10%-30% to ensure the integrity and stability of the SEI film, reducing side reactions between the electrolyte and the active material. Within this concentration range, FEC can significantly improve the electrochemical stability of the electrolyte, reducing the possibility of electrolyte decomposition, thereby improving the battery's cycle life and safety. A 10%-30% FEC content is also more compatible with the 1%-50% silicon-carbon material content of the total negative electrode active material, providing sufficient protection and support for the battery and ensuring stable operation at high energy densities.

[0099] Therefore, an FEC content of 10%-30% provides a balance between performance and cost, avoiding the increased cost and imbalance of other electrolyte components caused by an FEC content higher than 30%, while also avoiding insufficient formation of an effective SEI film when the FEC content is lower than 10%.

[0100] As is conceivable, the battery of the present invention also includes a positive electrode and a separator.

[0101] This invention does not strictly limit the positive electrode active material in the positive electrode sheet; it can be any positive electrode active material commonly used in lithium-ion batteries, such as at least one composite oxide of lithium with cobalt, manganese, nickel, or combinations thereof. More specifically, it can be at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, nickel-cobalt-manganese ternary materials, nickel-cobalt-aluminum ternary materials, lithium iron phosphate (LFP), lithium nickel manganese oxide, lithium-rich manganese-based materials, etc.

[0102] The present invention does not strictly limit the choice of electrolyte, and may include the electrolyte lithium salt commonly used in lithium-ion electrolytes, such as lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) or one or more of these.

[0103] This invention does not strictly limit the choice of separator material. It can be one of the separator materials commonly used in lithium-ion batteries, such as polypropylene separator (PP), polyethylene separator (PE), polypropylene / polyethylene double-layer composite membrane (PP / PE), polyimide electrospun separator (PI), polypropylene / polyethylene / polypropylene triple-layer composite membrane (PP / PE / PP), cellulose nonwoven separator, and separator with ceramic coating.

[0104] In the preparation of lithium-ion batteries, the positive electrode, separator, and negative electrode are wound or stacked to obtain a bare cell, which is then packaged into a pre-stamped aluminum-plastic film bag. After the packaged battery is dried at 85°C, the electrolyte is injected into the dried battery. The battery undergoes resting, formation, and secondary sealing to complete the preparation of the lithium-ion battery.

[0105] This invention also provides an electrical device including the battery described above. This electrical device has advantages corresponding to the electrolyte described above, which will not be elaborated further.

[0106] The electrical equipment used in the embodiments of the present invention can be conventional electrical equipment in the art, such as power equipment (e.g., electric vehicles, electric cars), electronic equipment (e.g., mobile phones, tablets, laptops, digital cameras, etc.), wearable devices (e.g., watches, bracelets, VR glasses, etc.), energy storage power stations, etc., and there are no particular limitations on this.

[0107] The invention provided by the present invention will be further described in detail below through specific embodiments.

[0108] It should be noted that, unless otherwise specified, the raw materials used in the following embodiments can be obtained by commercial purchase or conventional methods, and the experimental methods without specific conditions are all conventional methods and conditions well known in the art.

[0109] Example 1

[0110] (1) Preparation of positive electrode

[0111] Lithium cobalt oxide, polyvinylidene fluoride, and acetylene black were mixed in a mass ratio of 97:2:1, and N-methylpyrrolidone was added. The mixture was stirred under vacuum to obtain a positive electrode active slurry. The positive electrode active slurry was uniformly coated onto the surface of an aluminum foil with a thickness of 9 μm. After coating, the foil was dried and then rolled and slit to obtain a positive electrode sheet with a single-sided thickness of 54.5 μm and a double-sided thickness of 100 μm. The single-sided thickness and double-sided thickness of the positive electrode active material layer both include the thickness of the aluminum foil.

[0112] (2) Preparation of negative electrode sheet

[0113] A slurry was prepared using a wet process, consisting of single-walled carbon nanotubes, graphite, silicon, conductive carbon black, sodium carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 0.5:97:0.5:1.5:0.5. This slurry was coated onto both sides of a 6 μm thick copper foil used as a negative electrode current collector. After drying at 85°C for 5 h, the foil was rolled and die-cut to obtain a negative electrode sheet with a total thickness of 90 μm. The total solder area of ​​the negative electrode tabs was 15 mm². 2 The negative electrode tab area is 150mm². 2 The ratio B of the total solder area of ​​the negative electrode tab to the area of ​​the negative electrode tab groove is 10%.

[0114] (3) Electrolyte preparation

[0115] Based on the total mass of the electrolyte (100%), it includes: 1% lithium difluoroborate oxalate, 15% fluoroethylene carbonate, 15% lithium hexafluorophosphate, 5% nitrile additives (C, the mass percentage of nitrile additives in the electrolyte) (butadionitrile, 1,3,6-hexanetrionitrile and adiponitrile in a mass ratio of 1:3:1), 1% PS, 0.5% PST, 2% BDTD (the compound shown in Formula 7), 8% lithium bis(trifluoromethanesulfonylimide), 28.88% ethyl propionate and propyl propionate (A, the mass percentage of ethyl propionate and propyl propionate in the electrolyte) (mass ratio of ethyl propionate and propyl propionate is 25:30), and the remainder is a mixed solvent of ethylene carbonate, propylene carbonate and difluoroethyl acetate (mass ratio of ethylene carbonate, propylene carbonate and difluoroethyl acetate is 15:10:20).

[0116] In an argon-filled glove box, under conditions of H2O < 0.1 ppm and O2 < 0.1 ppm, ethylene carbonate, propylene carbonate, ethyl propionate, propyl propionate, and difluoroethyl acetate are mixed evenly. Then, thoroughly dried lithium salt is added and mixed evenly. After mixing evenly, other additives are added and stirred until the desired electrolyte is obtained.

[0117] 4) Preparation of lithium-ion batteries

[0118] After the positive electrode, separator, and negative electrode are stacked in sequence, they are wound to obtain a battery cell. The battery cell is placed in an outer packaging aluminum foil, and the electrolyte is injected into the outer packaging. After vacuum sealing, settling, formation, shaping, and sorting, a lithium-ion battery is obtained.

[0119] The following parameters are included in this embodiment: Ethyl propionate in the electrolyte (referred to as ethyl propionate in the table), propyl propionate in the electrolyte (referred to as propyl propionate in the table), A, total solder area of ​​the negative electrode tabs on the negative electrode sheet of the battery (referred to as total solder area of ​​the negative electrode tabs in the table), negative electrode tab area, B, A / B, C, 5C / B, PST in the electrolyte (referred to as PST in the table), PS in the electrolyte (referred to as PS in the table), BDTD in the electrolyte (referred to as BDTD in the table), sulfur-containing additives (including PST, PS, and BDTD) in the electrolyte (referred to as sulfur-containing additives in the table), and difluoroethyl acetate in the electrolyte (referred to as...). The mass percentages of lithium fluorocarbonate (DFEA), lithium fluorocarbonate (FEC), lithium difluoroborate oxalate (LiDFOB), the mass ratio of lithium fluorocarbonate to lithium difluoroborate oxalate, lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), ethylene carbonate, propylene carbonate, and the mass percentage of silicon carbon materials in the total mass of the negative electrode active materials are shown in Tables 1 and 2.

[0120] The differences between Examples 2-14, Comparative Examples 1-2 and Example 1 are: the mass percentage of ethyl propionate in the electrolyte (abbreviated as ethyl propionate in the table), the mass percentage of propyl propionate in the electrolyte (abbreviated as propyl propionate in the table), A, the total solder area of ​​the negative electrode tab on the negative electrode sheet of the battery (abbreviated as total solder area of ​​the negative electrode tab in the table), the area of ​​the negative electrode tab groove, B, A / B, C, 5C / B, the mass percentage of PST in the electrolyte (abbreviated as PST in the table), the mass percentage of PS in the electrolyte (abbreviated as PS in the table), the mass percentage of BDTD in the electrolyte (abbreviated as BDTD in the table), the mass percentage of sulfur-containing additives (including PST, PS, and BDTD) in the electrolyte (abbreviated as sulfur-containing additives in the table), and the mass percentage of difluoroethyl acetate in the electrolyte (abbreviated as DF in the table). The following parameters differ: the mass percentage of fluoroethylene carbonate in the electrolyte (referred to as FEC in the table), the mass percentage of lithium difluoroborate oxalate in the electrolyte (referred to as LiDFOB in the table), the mass ratio of fluoroethylene carbonate to lithium difluoroborate oxalate (referred to as FEC:LiDFOB in the table), the mass percentage of lithium hexafluorophosphate in the electrolyte (referred to as LiPF6 in the table), the mass percentage of lithium bis(trifluoromethanesulfonylimide) in the electrolyte (referred to as LiTFSI in the table), the mass percentage of ethylene carbonate in the electrolyte (referred to as ethylene carbonate in the table), the mass percentage of propylene carbonate in the electrolyte (referred to as ethylene carbonate in the table), and the mass percentage of silicon carbon material in the total mass of negative electrode active material (referred to as silicon carbon material mass percentage in the table). See Tables 1, 2, and 3 for details.

[0121]

[0122]

[0123]

[0124] Performance testing

[0125] (1) Lithium plating on the negative electrode of the battery

[0126] The batteries prepared in the above embodiments and comparative examples were subjected to lithium plating tests at room temperature, and the specific methods are as follows:

[0127] Under 25℃ conditions, the charging process was as follows: first, constant current charging at 3C to 4.55V, then constant voltage charging until the current dropped to 0.05C; the discharging process was as follows: constant current discharging at 1C to 3.0V; finally, charging at 3C to 4.55V, with 0.05C cutoff; after repeating 20 cycles, the battery was disassembled, and the lithium plating on the negative electrode was observed. The degree of lithium plating was ranked from lightest to heaviest as slight lithium plating, lithium plating, and severe lithium plating.

[0128] Specific judgment method: After the battery has undergone 500 cycles, it is fully charged and disassembled to observe the lithium plating at the arc of the negative electrode. The presence of only small dots or only slight gray lithium plating indicates slight lithium plating. The presence of obvious silver lithium plating connected in strips indicates severe lithium plating. If the negative electrode only has golden yellow negative electrode powder and the corresponding separator area is only white, it is judged as no lithium plating.

[0129] The test results are shown in Table 4 (degree of lithium plating).

[0130] (2) Cyclic performance test at 25℃

[0131] The batteries prepared in the above examples and comparative examples were subjected to 800 charge-discharge cycles at 25°C within the charge-discharge cutoff voltage range (3.0-4.55V) according to the 3C stepped charging rate. The discharge capacity of the first week was recorded as x1 mAh, and the thickness of the battery was recorded as y1. The discharge capacity of the 800th week was recorded as x2 mAh, and the thickness of the battery after the 800th week was recorded as y2. The cycle capacity retention rate of the 800th week was R1 = x2 / x1 (the capacity retention rate at 25°C in Table 4). The battery thickness expansion rate of the 800th week was H1 = (y2-y1) / y1 (the battery thickness expansion rate at 25°C in Table 4). The test results are shown in Table 4.

[0132] (3) Storage performance test at 85℃

[0133] First, let the batteries prepared by the above-mentioned examples and comparative examples after the formation and capacity test stand for 10 min, then discharge at 0.2C to 3.0V, stand for 10 min, then fully charge at 0.5C (upper limit voltage 4.55V), cut off at 0.05C, stand for 10 min, and test the fully charged voltage, internal resistance, and battery thickness y3 at 25±5℃.

[0134] After fully charging the battery, place it in an 85℃ oven for 6 hours. After removing it, test the voltage, internal resistance, and battery thickness y4. Perform capacity retention and recovery tests. Record the initial capacity as x3 and the residual capacity as x4. Thickness expansion rate H2=(y4-y3) / y3; Capacity retention rate R2=x4 / x3. The test results are shown in Table 4 (Residual capacity retention rate after 85℃ storage).

[0135] (4) Safety performance test at 130℃ furnace temperature

[0136] The batteries prepared in the above-mentioned examples and comparative examples after capacity testing were charged at 0.5C to the upper limit cutoff voltage of 4.55V, and then kept constant at 0.05C. The fully charged samples were placed in a thermal shock test chamber at an ambient temperature of 25±5℃, and then the temperature was increased to 130±2℃ at a rate of 15±2℃ / min and maintained at this temperature for 60 min before the test ended.

[0137] Observe whether the battery catches fire or explodes. If it does not catch fire or explode, the safety performance is marked as "passed". If it only catches fire, only explodes, or both catch fire and explode, the safety performance is marked as "failed". Record the pass status of the furnace temperature safety performance test. The pass status is shown in Table 4 (130℃ furnace temperature safety performance).

[0138] (5) Battery fast charging performance test

[0139] The batteries prepared in the above examples and comparative examples were tested for voltage, internal resistance, and battery thickness at a temperature of 25±5℃.

[0140] The testing steps are as follows:

[0141] 1) Let stand for 10 minutes;

[0142] 2) Discharge at 0.2C to the lower limit voltage;

[0143] 3) Let stand for 10 minutes;

[0144] 4) Charge to the upper limit voltage at a specific rate (charging rates are as follows: 1C / 2C / 3C / 4C), with a cut-off current of 0.025C;

[0145] 5) Let stand for 10 minutes;

[0146] 6) Discharge at 0.2C to the lower limit voltage;

[0147] 7) Let stand for 10 minutes;

[0148] Then repeat steps 4-7 until all rate charging tests are completed.

[0149] The constant current charging ratio at each rate was compared to test the fast charging performance. The constant current charging ratio at 4C rate was used as the performance test result. The test results are shown in Table 4 (Battery Fast Charging Performance).

[0150]

[0151] As shown in the table, compared with the comparative example, the embodiments of the present invention effectively improve the lithium plating problem of the negative electrode by adjusting the electrolyte composition of the battery and the ratio of the total solder area of ​​the negative electrode tab to the area of ​​the negative electrode tab groove. Compared with Examples 8-14, Example 1 of the present invention further improves the lithium plating problem of the negative electrode by further controlling the mass ratio of electrolyte components such as nitrile additives and sulfur-containing additives in the electrolyte.

[0152] Other embodiments of the invention will readily occur to those skilled in the art upon consideration of the specification and practice of the invention disclosed herein. This invention is intended to cover any variations, uses, or adaptations of the invention that follow the general principles of the invention and include common knowledge or customary techniques in the art not disclosed herein. The specification and examples are to be considered exemplary only, and the true scope and spirit of the invention are indicated by the following claims.

Claims

1. A battery, characterized in that, The battery comprises a positive electrode, a negative electrode, and an electrolyte. The organic solvent in the electrolyte includes ethyl propionate and propyl propionate. The positive electrode has at least two positive tabs. The negative electrode includes a negative current collector and a negative active layer disposed on the current collector. The active layer exposes a portion of the current collector and forms a negative tab groove. A negative tab is welded into the negative tab groove. The battery satisfies Equation 1: A / B≥2 Equation 1 In Formula 1, A is the sum of the mass percentages of ethyl propionate and propyl propionate in the electrolyte, expressed as %; B is the ratio of the total solder area of ​​the negative electrode tabs on the negative electrode sheet to the area of ​​the negative electrode tab groove, expressed as %; wherein, the total solder area of ​​the negative electrode tabs refers to the sum of the areas of all solders at the connection between the negative electrode tabs and the negative electrode current collector, and the area of ​​the negative electrode tab groove refers to the current collector area enclosed by the three sides of the negative electrode tab groove and the edge of the negative electrode current collector.

2. The battery according to claim 1, characterized in that, The negative electrode tab groove has a negative electrode active layer on three sides, and B is 5%-35%; And / or, the total solder area of ​​the negative electrode tab is 15 mm. 2 -50 mm², the negative electrode tab area is 150 mm². 2 -300mm 2 .

3. The battery according to claim 1 or 2, characterized in that, The electrolyte further includes nitrile additives, which include at least one selected from adiponitrile, 1,3,6-hexanetrionitrile, and butadionitrile, and the nitrile additives satisfy formula 2: 5C / B≥1 Equation 2 In Formula 2, C represents the mass percentage of nitrile additives in the electrolyte, expressed as %.

4. The battery according to claim 3, characterized in that, C is 0.5%-10%.

5. The battery according to any one of claims 1-4, characterized in that, The electrolyte further includes a sulfur-containing additive, which includes at least one of 1,3-propenesulfonate lactone, 1,3-propanesulfonate lactone, and BDTD, wherein BDTD includes at least one compound with the following structure: Formula 1, Equation 2, Formula 3, Equation 4, Equation 5, Formula 6, Equation 7, Formula 8, Formula 9, Formula 10, Formula 11, Equation 12, The sulfur-containing additive has a mass percentage content of 0.1%-6% in the electrolyte.

6. The battery according to any one of claims 1-5, characterized in that, A is 10%-80%; And / or, the electrolyte further includes difluoroethyl acetate, wherein the mass percentage of difluoroethyl acetate in the electrolyte is 3%-50%.

7. The battery according to any one of claims 1-6, characterized in that, The electrolyte includes a negative electrode film-forming agent, which includes fluoroethylene carbonate and / or lithium difluoroborate oxalate.

8. The battery according to claim 7, characterized in that, The mass ratio of the fluoroethylene carbonate to lithium difluoroborate oxalate is ≥10:1; And / or, the fluoroethylene carbonate has a mass percentage content of 2%-30% in the electrolyte, and the lithium difluoroborate oxalate has a mass percentage content of 0.1%-3% in the electrolyte.

9. The battery according to any one of claims 1-8, characterized in that, The negative electrode sheet comprises silicon-carbon material, the mass of which is 1-50% of the total mass of the negative electrode active material, and the content of fluoroethylene carbonate in the electrolyte accounts for 10%-30% of the total mass of the electrolyte.

10. An electrical appliance, characterized in that, Includes the battery as described in claim 9.